Washington View: As schools change, so should our policies. (May 2015) - Ferguson, Maria
Demographic projections call for America to become less white in the coming decades. By at least one measure, the percentage of students in U.S. schools who are white will fall below 50% within the next 10 years. As Asians, Latinos, and African Americans account for a greater portion of school children it is not entirely clear what policy changes will need to be made. In states that already have experienced these demographic shifts policy makers have changed education funding to support schools and students in low-income, minority areas. Indeed, schools need to be supported at both ends of the age spectrum. More and better preschool programs are needed and so is assistance to help Latinos and African Americans afford college.